Device and method for testing tangential ice adhesion strength on surface of base material
By designing the optimized mold and force measuring rod structure, combined with low-density and high-strength materials and the balanced temperature adjustment of the temperature control chamber, the problem of ice adhesion strength measurement error in the existing technology is solved, and more accurate ice adhesion strength is achieved Measurement.
Patent Information
- Application Number
- CN202411283287.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing ice adhesion strength measurement devices have measurement errors caused by inappropriate wall thickness and material of small barrels. The leakage of clean water causes inaccurate icy area, which affects the accuracy of the measurement results.
A test device for the tangential ice adhesion strength of the substrate surface is designed, using a mold, a force measuring rod and a temperature control chamber, which minimizes the wall thickness of the mold to reduce self-weight, and the force measuring rod is perpendicular to the contact point of the probe to reduce torque, and liquid Injection is carried out in batches to avoid leakage. The materials are selected as low-density and high-strength materials such as graphite and polypropylene. The temperature control chamber is balanced to adjust the temperature to shorten the solidification time.
Improves the accuracy of ice adhesion strength measurement, reduces measurement errors, and ensures the reliability and accuracy of the results.
Smart Images

Figure CN119147457A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to ice adhesion strength measurement, in particular to a test device and method for the tangential ice adhesion strength of a substrate surface. Background Art
[0002] Power security is the foundation of energy security. Disasters caused by changing climate and environment will pose serious threats to power security, and icing is one of them. my country's power transmission lines are the longest and largest in the world, and the voltage level is the highest in the world. A large number of transmission lines will cross low temperature, high humidity, high altitude and other environments, which are prone to icing disasters, causing power equipment disconnection, tower collapse and other problems, resulting in large-scale power outages and even collapse, threatening the safe and stable operation of the power grid. At the same time, with the rise of the new energy industry, the scope of wind power development is also expanding. These areas with rich wind power energy are often accompanied by extreme weather that is cold and easy to ice, which also increases the demand for anti-icing technology for wind turbine blades.
[0003] The development of anti-icing technology is inseparable from the progress of research techniques. Our country's research in this area is still relatively basic. Before we can completely solve the icing problem of outdoor equipment, there are still many problems to be overcome. The accurate characterization of icing intensity can provide researchers with good research feedback.
[0004] The Chinese invention patent application with publication number CN117054331A discloses a fully automatic test device and method for detecting frozen adhesion of material surface. The test device includes a low-temperature heat-insulated sealed test chamber 1, a high-definition camera 2, a small bucket freezing mechanism 3, a refrigerated temperature-controlled sample fixing table 4, an adhesion probe 5, a mechanical sensor 6, an electric displacement stage 7, and a system control software program 8. First, the test sample is fixed on the refrigerated temperature-controlled fixing table; then the small bucket freezing mechanism is placed at the position to be tested and water is injected, and the contact surface is frozen and adhered stably; finally, the start test button is pressed on the software end, and the system automatically controls the electric displacement stage to move in a uniform linear motion, and the probe collides with the small bucket freezing mechanism to peel it off from the sample surface, and the data of the mechanical sensor is recorded in real time, and the system software automatically calculates the adhesion strength, adhesion and other parameters. The device of the invention is equipped with precise detection elements, which can avoid previous experimental errors and environmental interference, and can intuitively, realistically and automatically characterize the adhesion of the material surface to explore the interaction between different surface structures and frozen adhesion.
[0005] Although the above-mentioned device can also measure the ice adhesion strength, the wall thickness of the bucket, its overall size and the material of the bucket are not clearly defined. If the wall thickness of the bucket is too thick, the weight of the bucket will increase the friction between the bucket and the sample to be tested under the same contact area between the ice layer and the sample to be tested, so that the force required to push the bucket will be greater, which will increase the error of the final measurement result. Inappropriate bucket material will also increase its own weight and increase the error of the final measurement result. In addition, the contact position between the adhesion probe and the bucket is not clearly defined. When the contact position between the adhesion probe and the bucket is biased upward, additional torque will be generated, resulting in an increase in the error of the measurement result. In addition, the clean water is placed directly in the bucket. Before it freezes, it is easy for the clean water to leak and spread along the surface of the bucket and the sample to be tested, resulting in the final ice area being larger than the contact area between the bucket and the sample to be tested, making the measurement result inaccurate. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a testing device and method for the tangential ice adhesion strength of a substrate surface which can accurately measure the ice adhesion strength.
[0007] Technical solution: The testing device for the tangential ice adhesion strength of the substrate surface described in the present invention includes a mold, a force measuring rod, a power device for driving the force measuring rod to move, and a temperature control chamber. The bottom opening of the mold is placed on the top of the sample to be tested. The mold is provided with a liquid injection port. The wall thickness of the mold is the minimum value that meets the overall strength requirement. The axis of the force measuring rod and the normal direction of the contact point between the front end probe and the mold are perpendicular to the axis of the mold, and the probe is flush with the lowermost end of the mold.
[0008] Based on the above technology, the mold is provided with a liquid injection port to inject clean water or other liquids to be tested into it in batches to avoid excessive liquid in the mold. Before the bottom liquid solidifies, it leaks and spreads along the contact surface with the sample to be tested, resulting in the actual contact area between the ice layer and the sample to be tested being larger than the area at the bottom of the mold cavity. The increase in the actual contact area with the ice layer will require a greater force to push the mold, causing measurement errors. The thickness of the mold is the minimum value that meets the overall strength requirements, which can not only ensure that the overall strength of the mold will not be deformed and damaged under the action of external forces, but also reduce its own weight as much as possible to avoid the increase in the mold's own weight and the surface of the sample to be tested. The friction of the surface affects the final test result; the axis of the force measuring rod and the normal direction of the mold contact point at the front end of the probe are perpendicular to the axial direction of the mold, which can avoid that the force applied by the force measuring rod to the mold is only used to promote its translation without part of the force promoting the mold to rotate, causing measurement errors; the probe is flush with the lower end of the mold, which minimizes the distance from the force application point of the force measuring rod to the lower end of the mold, avoids the applied force from becoming a torque that promotes the mold to rotate in the vertical plane, and reduces the force measurement error; in summary, the structure of the mold and the force measuring rod of the present application can minimize the measurement error and improve the measurement accuracy.
[0009] Preferably, the temperature-controlled chamber can evenly adjust the temperature inside the chamber.
[0010] This can solidify the liquid in the mold in a shorter time and avoid cooling starting from the contact surface between the mold and the sample to be tested. The liquid in the upper layer of the mold takes a long time to solidify and may not be completely solidified if there is not enough time, causing measurement errors.
[0011] Preferably, the material of the mold is any one of graphite, polypropylene, polyethylene, polytetrafluoroethylene and polymethyl methacrylate, or any combination thereof.
[0012] The above materials have low density and high strength and are not easily deformed or damaged. At the same time, they can reduce the weight of the mold and reduce the influence of the mold's own weight on the measurement results.
[0013] Preferably, the mold is cylindrical, and its wall thickness d satisfies d≤1 / 5R, where R is the outer diameter of the mold.
[0014] The wall thickness of the mold meets the above conditions, which can not only meet the overall strength requirements but also minimize the deadweight.
[0015] Preferably, a storage table is provided in the temperature-controlled chamber, the surface of the storage table is horizontal, and a fixing piece for fixing the sample to be tested is provided on the surface.
[0016] Setting up a storage table can place the mold and the sample to be tested in the center of the temperature control chamber, which can better balance the cooling.
[0017] Preferably, the force measuring rod is connected to a digital dynamometer, the digital dynamometer is connected to a power device, and the power device adopts a slide table.
[0018] Preferably, the power device and the digital dynamometer are located outside the temperature-controlled chamber, the dynamometer rod is slidably connected to the side wall of the temperature-controlled chamber, and a sealing ring is provided at the connection between the two.
[0019] The power device and the digital dynamometer are located outside the temperature control chamber, which can reduce the volume of the temperature control chamber and reduce energy consumption; a sealing ring is provided at the connection between the dynamometer rod and the temperature control chamber to ensure the sealing of the temperature control chamber.
[0020] The method for testing the tangential ice adhesion strength of a substrate surface of the present invention comprises the following steps:
[0021] S1. Place the sample to be tested and the mold in a temperature-controlled chamber;
[0022] S2, dripping the liquid to be tested into the mold twice, waiting for the liquid to solidify after the liquid level of the first dripping reaches the set value, and then dripping the liquid to be tested again until the liquid level reaches the set value;
[0023] S3, after the liquid in the mold is completely solidified, the power device is turned on to move the force measuring rod at a set speed, and the force applied when the mold moves is recorded to calculate the tangential ice adhesion strength;
[0024] S4. Repeat steps S1-S3 to measure multiple tangential ice adhesion strength values of the same sample to be tested, remove abnormal values and take the average value as the final tangential ice adhesion strength of the sample to be tested.
[0025] Based on the above measurement method, the liquid to be tested is dripped into the mold twice. The first dripping amount is relatively small, which can prevent the liquid from leaking from the bottom of the mold, making the actual ice layer area larger than the area of the bottom of the mold cavity, causing measurement errors, thereby improving the accuracy of the final measurement.
[0026] Preferably, in step S2, before dripping the test liquid into the mold, the horizontality of the contact surface between the test sample and the mold is adjusted to meet the set requirements.
[0027] Before dripping the liquid to be tested, the horizontality of the contact surface between the sample to be tested and the mold should be adjusted to avoid the unevenness of the plane and the subsequent ice layer, which will make it impossible to accurately measure the tangential ice adhesion.
[0028] Preferably, the calculation formula for the tangential ice adhesion strength in step S3 is as follows:
[0029]
[0030] Among them, F is the force applied by the force rod when the mold moves, and r is the inner diameter of the mold.
[0031] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: a water injection port is set in the mold and the thickness is minimized while meeting the strength requirement; the force measuring rod and the contact point position of the probe at its front end with the mold can improve the measurement accuracy of ice adhesion, thereby improving the final measurement accuracy; in the measurement method, the liquid to be measured is dripped in twice to avoid liquid leakage, which also improves the measurement accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is the overall structural diagram of this device. DETAILED DESCRIPTION
[0033] As shown in the figure, the testing device for the tangential ice adhesion strength of the substrate surface described in the present invention includes a mold 1, a force measuring rod 2, a power device 3 for driving the force measuring rod 2 to move, and a temperature control chamber 4. The bottom opening of the mold 1 is placed on the top of the sample to be tested. The mold 1 is provided with a liquid injection port. The wall thickness of the mold 1 is the minimum value that meets the overall strength requirement; the axis of the force measuring rod 2 and the normal direction of the contact point between the front end probe and the mold 1 are perpendicular to the axis of the mold 1, and the probe is flush with the lowermost end of the mold 1.
[0034] The material of the mold 1 is any one of graphite, polypropylene, polyethylene, polytetrafluoroethylene and polymethyl methacrylate or any combination thereof, which can meet the strength requirements and reduce the dead weight; the mold 1 is cylindrical, and its wall thickness d satisfies d≤1 / 5R, where R is the outer diameter of the mold 1, and the top and bottom of the mold 1 are both opened, and the top opening is used as the liquid injection port.
[0035] The force measuring rod 2 is connected to a digital dynamometer 6, which is connected to a power device 3. The power device 3 adopts a slide, and the digital dynamometer 6 is linked to the slider of the slide. According to actual needs, a raising platform 7 can be arranged at the bottom of the slide to adjust the force measuring rod 2 to a suitable height so that the probe at its front end meets the position requirements; the slide is connected to a control console 8 for controlling the movement speed of its slider; the test accuracy of the digital dynamometer 6 is at least 0.01N, it has a peak value display function, and data transmission can be performed; the slider of the slide meets the slowest moving speed v≤0.001mm / s.
[0036] The power device 3 and the digital dynamometer 6 are located outside the temperature control chamber 4, the dynamometer rod 2 is slidably connected to the side wall of the temperature control chamber 4, and a sealing ring is provided at the connection between the two; the power device 3 and the digital dynamometer 6 can also be arranged in the temperature control chamber 4, but in this case the volume of the temperature control chamber 4 will be increased accordingly.
[0037] The temperature-controlled chamber 4 can evenly adjust the temperature in the chamber. The controllable temperature of the temperature-controlled chamber 4 is between -20°C and 5°C, with an error of 0.5°C or less, and has a real-time temperature display function. The temperature-controlled chamber 4 can adopt a structure similar to an air-cooled refrigerator to achieve internal balanced cooling. A camera can also be provided in the temperature-controlled chamber 4 to observe and record the solidification of the liquid in the mold 1 in real time, and an observation window can also be provided on the temperature-controlled chamber 4 to observe the solidification of the liquid in the mold 1. The observation window is made of transparent insulation material, such as aerogel.
[0038] A storage table 5 is provided in the temperature control chamber 4. The surface of the storage table 5 is horizontal and is provided with fixing parts for fixing the sample to be tested. By adjusting the size of the storage table 5, the sample to be tested and the mold 1 can be placed at the center of the temperature control chamber 4, so that the liquid in the mold 1 can be cooled more evenly. The fixing parts can be two fixing bars and multiple fixing screws. When in use, the sample to be tested is first placed at a preset position on the storage table 5, and then the fixing bars are tied at both ends of the sample to be tested, and the fixing bars are fixed to the storage table with fixing screws to fix the sample to be tested.
[0039] The method for testing the tangential ice adhesion strength of a substrate surface according to the present invention comprises the following steps:
[0040] S1. Place the sample to be tested and the mold 1 in a temperature-controlled chamber 4.
[0041] The method for preparing the sample to be tested includes but is not limited to preparing the sample to be tested that meets the size requirements by cutting the sample as a whole, and ensuring the flatness and integrity of the sample surface to be tested; after the sample to be tested is prepared, it is fixed on the storage table 5 using a fixing frame, and then the mold 1 is placed on the top of the sample to be tested, and the temperature control chamber 4 begins to cool down, and the temperature is dropped to the set temperature for a certain time, such as 30 minutes before the next step is performed, so that the temperature of the mold 1 and each part of the sample to be tested can be kept consistent, so that the subsequent liquid can solidify evenly.
[0042] S2. Drop the liquid to be tested into the mold 1 twice. After the liquid level of the first drop reaches the set value, wait for it to solidify, and then drop the liquid to be tested again until the liquid level reaches the set value. The set value here can be two-thirds of the height of the mold 1.
[0043] The liquid to be tested is normally clean water, but can also be salt water or other liquids. If it is necessary to measure the ice adhesion strength of other specific liquids, the corresponding liquids can also be dripped in. Before dripping the liquid to be tested, it is necessary to first check whether the levelness of the contact surface between the sample to be tested and the mold 1 meets the requirements. If it does not meet the requirements, it is necessary to adjust its levelness to avoid affecting the levelness of the subsequent ice layer. If the ice layer is not level, the thickness of the ice layer will be uneven, and the measured ice adhesion will be inaccurate, affecting the final measurement result. The second liquid level height setting value is smaller than the height of the mold 1 in order to prevent the liquid solidification volume from increasing beyond the top of the mold 1.
[0044] The height of the liquid level h1 ≤ 1 mm for the first dripping, so that a thin layer of liquid can completely cover the bottom of the entire cavity of the mold 1 and solidify quickly without leaking out of the mold 1. When the liquid is dripped in for the second time, because there is already a layer of ice at the bottom to prevent leakage, a larger amount can be dripped in at one time until the set height requirement is met.
[0045] S3, after the liquid in the mold 1 is completely solidified, the power device 3 is turned on to move the force measuring rod 2 at a set speed, and the force applied by the mold 1 when moving is recorded to calculate the tangential ice adhesion strength; the force applied by the mold 1 when moving is the ice adhesion force F, and the calculation formula of the ice adhesion strength P is:
[0046]
[0047] Wherein, r is the inner diameter of the mold 1.
[0048] S4. Repeat steps S1-S3 to measure multiple tangential ice adhesion strength values of the same sample to be tested, remove abnormal values and take the average value as the final tangential ice adhesion strength of the sample to be tested.
[0049] In order to better illustrate the effect of the present invention, several specific experimental data are described below:
[0050] The samples to be tested are steel sheet, sandblasted steel plate, smooth aluminum sheet and polytetrafluoroethylene, respectively. The device and method of the present invention are used to measure the samples, and the measured values shown in Table 1 are obtained.
[0051] Table 1 Ice adhesion strength measurement records
[0052]
[0053] Among them, 756.45 in Example 2 is removed as an abnormal value and then the average value is calculated. From the above data, it can be seen that the maximum ratio of the deviation to the average value in all embodiments is 1.54%, and the degree of deviation is small. It can be considered that each measurement data is accurate. The device and method can achieve accurate measurement of ice adhesion strength.
Claims
1. A testing device for the tangential ice adhesion strength of a substrate surface, comprising a mold (1), a force measuring rod (2), a power device (3) for driving the force measuring rod (2) to move, and a temperature control chamber (4), wherein the bottom opening of the mold (1) is placed on the top of a sample to be tested. Features: The mold (1) is provided with a liquid injection port, and the wall thickness of the mold (1) is the minimum value that meets the overall strength requirements; the axis of the force measuring rod (2) and the normal direction of the contact point between the front end probe and the mold (1) are perpendicular to the axis of the mold (1), and the probe is flush with the lower end of the mold (1).
2. A test device for the tangential ice adhesion strength of a substrate surface according to claim 1, Features: The temperature-controlled chamber (4) can evenly adjust the temperature inside the chamber.
3. A testing device for the tangential ice adhesion strength of a substrate surface according to claim 1, Features: The material of the mold (1) is any one of graphite, polypropylene, polyethylene, polytetrafluoroethylene and polymethyl methacrylate, or any combination thereof.
4. A test device for the tangential ice adhesion strength of a substrate surface according to claim 3, Features: The mold (1) is cylindrical, and its wall thickness d satisfies d≤1 / 5R, where R is the outer diameter of the mold (1).
5. A testing device for the tangential ice adhesion strength of a substrate surface according to claim 1, Features: A storage platform (5) is provided in the temperature control chamber (4); the surface of the storage platform (5) is horizontal and is provided with fixing parts for fixing the sample to be tested.
6. A testing device for the tangential ice adhesion strength of a substrate surface according to claim 1, Features: The force measuring rod (2) is connected to a digital dynamometer (6), and the digital dynamometer (6) is connected to a power device (3), and the power device (3) adopts a slide table.
7. A testing device for the tangential ice adhesion strength of a substrate surface according to claim 6, Features: The power device (3) and the digital display dynamometer (6) are located outside the temperature control chamber (4), the dynamometer rod (2) penetrates and is slidably connected to the side wall of the temperature control chamber (4), and a sealing ring is provided at the connection between the two.
8. A method for testing the tangential ice adhesion strength of a substrate surface using the device of any one of claims 1 to 7, It is characterized in that The following steps are involved: S1, placing the sample to be tested and the mold (1) in a temperature-controlled chamber (4); S2, dripping the liquid to be tested into the mold (1) twice, waiting for the liquid to solidify after the liquid level reaches the set value after the first dripping, and then dripping the liquid to be tested again until the liquid level reaches the set value; S3, after the liquid in the mold (1) is completely solidified, the power device (3) is turned on to move the force measuring rod (2) at a set speed, and the force applied when the mold (1) moves is recorded to calculate the tangential ice adhesion strength; S4. Repeat steps S1-S3 to measure multiple tangential ice adhesion strength values of the same sample to be tested, remove abnormal values and take the average value as the final tangential ice adhesion strength of the sample to be tested.
9. The method for testing the tangential ice adhesion strength of a substrate surface according to claim 8, Features: The step S2 is to adjust the levelness of the contact surface between the sample to be tested and the mold (1) to meet the set requirements before dripping the liquid to be tested into the mold (1).
10. The method for testing the tangential ice adhesion strength of a substrate surface according to claim 8, Features: The calculation formula of the tangential ice adhesion strength in step S3 is as follows: Among them, F is the force applied by the force rod when the mold moves, and r is the inner diameter of the mold.
Citation Information
Patent Citations
Integrated experimental device and method for fully automatically detecting freezing adhesive force on surface of material
CN117054331A
Cited By
Ice bonding strength testing system with multi-parameter coordinated regulation and control
CN119757189A
